The Collaborative African Genomics Network (CAfGEN): Applying Genomic technologies to probe host factors important to the progression of HIV and HIV-tuberculosis infection in sub-Saharan Africa [version 1; referees: awaiting peer review] - Mboowa, Gerald; Mwesigwa, Savannah; Katagirya, Eric; Retshabile, Gaone; Mlotshwa, Busisiwe C.; Williams, Lesedi; Kekitiinwa, Adeodata; Kateete, David; Wampande, Eddie; Wayengera, Misaki; Nsangi Kintu, Betty; Kisitu, Grace P.; et al. (AAS open research, 2018)
The Human Heredity and Health in Africa consortium (H3Africa) was conceived to facilitate the application of genomics technologies to improve health across Africa. Here, we describe how the Collaborative African Genomics Network (CAfGEN) of the H3Africa consortium is using genomics to probe host genetic factors important to the progression of HIV and HIV-tuberculosis (TB) coinfection in sub-Saharan Africa. Methods: CAfGEN is an H3Africa collaborative centre comprising expertise from the University of Botswana; Makerere University; Baylor College of v
Keywords: Bioinformatics; Genetics; Genomics; HIV/AIDS; Pediatrics; Tuberculosis